Moral Suasion and the Private Provision of Public Goods: Evidence from the COVID-19 Pandemic - Björn Bos; Moritz A. Drupp; Jasper N. Meya; Martin F. Quaas (Environmental and Resource Economics, 2020)
We study how moral suasion that appeals to two major ethical theories, Consequentialism and Deontology, affects individual intentions to contribute to a public good. We use the COVID-19 pandemic as an exemplary case where there is a large gap between private and social costs and where moral suasion has been widely used as a policy instrument. Based on a survey experiment with a representative sample of around 3500 Germans at the beginning of the pandemic, we study how moral appeals affect contributions with low and high opportunity costs, hand washing and social distancing, to reduce the infection externality as well as the support for governmental regulation. We find that Deontological moral suasion, appealing to individual moral duty, is effective in increasing planned social distancing and hand-washing, while a Consequentialist appeal only increases planned hand-washing. Both appeals increase support for governmental regulation. Exploring heterogeneous treatment effects reveals that younger respondents are more susceptible to Deontological appeals. Our results highlight the potential of moral appeals to induce intended private contributions to a public good or the reduction of externalities, which can help to overcome collective action problems for a range of environmental issues.
Keywords: C93; D62; D64; H41; I18; Q58; 330; COVID-19; Coronavirus; Public good contributions; Moral appeal; Moral suasion